Stem Cell Therapy for the Treatment of Hip Osteonecrosis: A 30-Year Review of Progress - Hernigou, Philippe; Trousselier, Matthieu; Roubineau, François; Bouthors, Charlie; Chevallier, Nathalie; Rouard, Helene; Flouzat-Lachaniette, Charles Henri (Clinics in orthopedic surgery, 2016)
Avascular necrosis of the femoral head is caused by a multitude of etiologic factors and is associated with collapse with a risk of hip arthroplasty in younger populations. A focus on early disease management with the use of stem cells was proposed as early as 1985 by the senior author (PH). We undertook a systematic review of the medical literature to examine the progress in cell therapy during the last 30 years for the treatment of early stage osteonecrosis.